Laser drilling of composite material : A review - Khairul Fikri, Bin Tamrin; Sheikh, N. A.; Sapuan, S. M. (Elsevier Ltd., 2019)
Carbon fiber reinforced polymer (CFRP), glass fiber reinforced polymer (GFRP) and fiber metal laminate (FLM) are some examples of composite laminates. They are attractive for many applications (such as aerospace and aircraft structural components) due to their superior properties. However, composite laminates are regarded as hard-to-machine materials, which results in low drilling efficiency and undesirable drilling-induced delamination. As non-contact and wear-less machining tools, lasers represent a favorable alternative in processing various types of composites, which are inherently anisotropic and extremely abrasive materials. In addition, this chapter covers a number of laser drilling methods (percussion, trepanning and multiple-rings trepanning) and their effects on hole properties. In particular, this chapter examines the applications of various ultrashort laser pulses (picosecond and femtosecond) for composite material drilling, and discusses the effect of underwater laser drilling. In the past decade, several new materials and manufacturing processes have been proposed and developed. A new class of structural materials, ceramic matrix composites (CMC), has emerged with the carbon fibres based reinforcements along with silicon carbide matrices (C/SiC or C/C-SiC composites). C/SiC composites have several features such as having reinforcements of relatively shorter lengths, cheap polymer precursors and liquid phase processes; these features reduce their costs by almost one order of magnitude. Lasers have long been employed in several machining and fabrication processes. Metals have been usual target materials for their applications; however, recently laser applications for dissimilar materials have been extensively studied.